High-efficiency, environment-friendly moss-enriched microbial fuel cell - Cek, Nurettin; Erensoy, Ahmet; Ak, Namdc; Demirbas, Ayhan; Gorgulu, Ahmet Orhan; Uslu, Hasan (Walter de Gruyter Gmbh, 2022)
Microbial fuel cells (MFCs) can be used to produce clean energy from organic wastes. Various biomasses for MFCs can be used as biofuel materials. Moss (Bryophyta) is a source of biomass materials and can be used as an alternative fuel for microbial fuel cells. In this study, moss-enriched MFCs were produced by using moss as a biofuel source and aluminum and silver as an electrode. As a result of the good electrochemical performance of the metal electrodes (aluminum and silver), higher power density than previous studies involving moss was obtained, with the highest power density in this study being 20 mW/m(2). Moreover, in this study, bacterial activity, biofilm formation, soil utilization, pH change, and corrosion were investigated in MFCs and the effects of MFC on power density were discussed. The addition of soil increased the corrosion rate and internal resistance while reducing the power density. As a result of the addition of soil, the power density dropped to 16.13 mW/m(2). The corrosion rate was lower than industrial corrosion. Changes in pH confirmed that organic material dissolved and chemical reactions took place. Scanning electron microscope (SEM)-Energy dispersive spectroscopy (EDS) analyzes showed the presence of Bacillus and Coccus bacteria species on the electrode surfaces. These bacteria were acted as biocatalysts by forming a biofilm on the electrode surfaces.
Keywords: biomass; clean energy; metal electrode; microbial fuel cell; moss